Pembuatan Label Kemasan Sebagai Bentuk Pemasaran pada UMKM Kerupuk Singkong - Ramadhani, Miagasela Aprilia (Maliki Interdisciplinary Journal, 2025)
The low awareness of Micro, Small and Medium Enterprises (MSME) actors regarding the importance of labels on applicable MSME product packaging, most MSME actors experience difficulties in paying attention to sticker labels on product packaging. Sticker labels on product packaging have an important role in increasing the attractiveness and selling value of a product, especially for Micro, Small and Medium Enterprises (MSMEs). This activity aims to obtain information about marketing strategies through making sticker labels on packaging for MSME cassava cracker products. Attractive and informative sticker label designs can improve product image, build brand awareness, and expand market reach. The methods used include observation, interviews with MSME actors. The results show that the use of sticker labels with attractive designs, appropriate colors and clear information can increase product competitiveness on the market. Thus, making sticker labels is not only a product identity, but also an effective marketing strategy in increasing sales of cassava cracker MSMEs.